Are Sustainable Consumers Health Conscious? A Segmentation Study of Wine Consumers. Issue 6 (24th July 2019) - Ghvanidze, Sophie; Velikova, Natalia; Dodd, Tim H.; Oldewage-Theron, Wilna
ABSTRACT: As a result of consumers' increasing concerns with ethical, environmental, and health issues, sustainable consumption and production have become a popular topic of recent academic research and industry practices. The current study sought to provide in-depth insights into consumers' views on sustainability by simultaneously examining their environmental and social awareness and behavior, health-conscious lifestyles, and diets; as well as the perceived importance of social and nutrition information on wine labels. Based on empirical data obtained through a web-based survey distributed to consumer panels in three markets – the US, the UK, and Germany – this research segmented wine consumers into four categories: Apathetic Consumers; Health-Conscious Diners; Holistic Perfectionists ; and Ethical Advocates . The findings indicate that in general wine consumers are mindful about the environmental problems, social responsibility of companies, ethically produced and sustainably sourced products. The majority adhere to healthy lifestyles and watch their diets. Nevertheless, with the exception of only one cluster (Holistic Perfectionists), wine consumers do not actively seek social, environmental, or nutritional information on wine labels. This study shows that, at least currently, the preferences for the social factors are unlikely to outweigh dominating traditional wine purchase drivers, such as price, brand, country of origin, and grape variety. Industry implications for tailored marketing strategies are discussed.